Feasibility Test Based on Insulation, Ratio and Internal Protection for 20 MVA Power Transformer of 150/20 kV Substation - Ramadhan, Fajar Bagus; Haddin, Muhamad (Institut Teknologi Dirgantara Adisutjipto, 2025)
The problems that occur in 20 MVA power transformers are insulation feasibility issues, voltage regulation and internal relay malfunctions. The impact is to cause a degradation of transformer reliability. The solution is how to ensure the feasibility of the transformer by evaluating the transformer feasibility test including the insulation subsystem, voltage ratio, and internal relay. This research discusses the feasibility of a 20 MVA transformer based on insulation, voltage ratio and internal relay. The model is a set of 20 MVA transformer GI 150 kV. The test method is carried out using polarization index, tangent delta, breakdown voltage, voltage ratio and sudden pressure relay function test. The references of all test methods are IEEE Std 62-1995 standard for polarization index, CIGRE TB 445 for tangent delta, IEC 60156-02-1995 for breakdown voltage, IEEE C57.125.1991 standard for voltage ratio and internal relay test validated using Proteus application. The test methods proved effective for evaluating the 20 MVA transformer feasibility test. This is evidenced by the worst value of 1.06 in testing the polarization index of the secondary to tertiary winding. Then 0.53% of tap voltage ratio 17 phase T and 0.58% of tap voltage ratio 18 phase T. The internal relay works as it should. The results obtained, the transformer is in an unfit condition and there needs to be further investigated so that it can be normally operated.